Present condition and perspective of the integrated information-computer network of Kyiv International University of Civil Aviation - Белецкий, А. Я.; Лупандин, М. В.; Лукгьяненко, O. E.; Ярмоленко, A. M. (Proceedings of National Aviation University (archive), 1998)
Considered are the principles of construction of information computer network (JCN) of Kyiv International University of Civil Aviation (KIUCA) which forms a part of information- communication network of higher education institutions of Ukraine with a system of distributed data bases of scientific, educational, industrial and commercial function. Given is a short historical review of main stages in formation and establishment of JCH of KIUCA from the very beginning to the present configuration of JCH. Touched upon are problems of integration of information computer network of KIUCA into Internet